Bacterial-charged biochar enhances plant growth and mitigates microplastic toxicity by altering microbial communities and soil metabolism - Muhammad Afzal; Xiyu Tan; Yihang Ouyang; Yihang Chen; Qihua Liang; Mehmood Jan; Arif Ali Khattak; Xiaolin Wang; Xiaoyuan Chen; Xiaoying Zhang; Zhiyuan Tan (Plant Stress, 2025)
Microplastic (MP) contamination in agricultural soils is an emerging global concern, with levels in China’s paddy soils ranging from 1300 to over 15,000 particles kg−1, and up to 40,000 particles kg−1 in farmland. This pollution threatens sustainable agriculture by impairing plant growth and disrupting plant-microbe interactions. This study evaluated the remediation potential of bacteria with MPs (Bac_MP), biochar with MPs (Bcr_MP), and bacteria plus biochar with MPs (BBM) in paddy soils, assessing their effects on rice (Oryza sativa L.) physiology, soil biochemistry, rhizosphere microbiome, and metabolome. Using qPCR, high-throughput sequencing, and untargeted metabolomics, we examined gene expression, microbial diversity, and metabolomic profiles. BBM significantly enhanced plant growth, increasing shoot fresh and dry weights by 115 % and 161 %, respectively, and raised protein content to 39 nmol g⁻¹ fresh weight. It mitigated oxidative stress by reducing malondialdehyde levels and moderately increasing antioxidant enzyme activities. Soil phosphorus availability increased 2.41-fold, with significant improvements in nitrification (p ≤ 0.05). BBM upregulated nitrogen transporter genes OsNTR1.1 and OsNTR1.2 by 13- and 10.5-fold, and phosphorus transporter genes OsPT1 and OsPT8 by 12- and 9-fold. Microbiome and metabolome analyses revealed enrichment of beneficial bacterial and fungal phyla, including Proteobacteria, Firmicutes, Gemmatimonadetes, Ascomycota, and Basidiomycota, along with key metabolites linked to nutrient cycling and stress tolerance. The bacterial genus Bacillus increased in all treatments, with Kaistobacter, Anaerolinea, and Flavisolibacter enriched under BBM. Notably, the fungal genus Humicola increased 41-fold. These findings highlight BBM as a promising strategy for remediating MP-contaminated soils, improving soil fertility, and supporting sustainable agriculture.